SNG production with net zero outflow of CO2 in an integrated energy system: An energy and economic aspects. (15th October 2022) - Haider, Junaid; Lee, Boreum; Choe, Changgwon; Abdul Qyyum, Muhammad; Shiung Lam, Su; Lim, Hankwon
Highlights: An integrated energy system of SNG production is proposed with net zero CO2 outflow. SOEC–based water electrolysis was used which accounts specific power 35.56 kW/kgH2. Heat recovery from SNG production was achieved by Rankine cycles with 1.8 MW power. Efficiency of proposed integrated system for PtM technology was obtained as 77.3% SNG unit production price was calculated as 0.223 $/kWh. Abstract: Integrated energy systems are getting high attention due to their synergistic effects on both the energy efficiency and process economy. This study demonstrates the similar effect of coupling four processes such as solid oxide electrolyzer cell (SOEC)-based hydrogen production from renewable energy, synthetic natural gas (SNG) production, steam Rankine cycle (SRC) for energy recovery, and amine-based SNG upgrading. Integration of two SRCs with SNG produces 1.8 MW of power that is assumed to reduce the load on SOEC. In addition, monoethanol amine (MEA)-based chemical absorption provides two benefits comprising SNG upgrading and capture of unreacted CO2 . The proposed process integration claims the net zero output of CO2 in purified SNG stream as the captured CO2 is recycled back to the SNG reaction system for process enhancement. Conclusively, proposed integrated process synergistically enhances the SNG production efficiency by up to 86 % while the whole integrated process efficiency is calculated at 77.3 %. Corresponding to process economy, unit production price of SNG is observed to be 0.223 $/kWh, which is comparable to other existing processes. Moreover, methane parity analysis and future predictions are made with expected natural gas price to estimate the possible reliance on SNG in coming decades.